Ranging behaviour of Long-crested Eagles Lophaetus occipitalis in human-modified landscapes of KwaZulu-Natal, South Africa. (2nd July 2020) - Maphalala, Machawe I; Monadjem, Ara; Bildstein, Keith L; McPherson, Shane; Hoffman, Ben; Downs, Colleen T
Abstract : The ranging behaviour of raptors in human-altered environments, such as agricultural and suburban landscapes, is becoming increasingly important for conservationists in the context of unprecedented high rates of anthropogenic land use change. We studied the movement ecology of adult Long-crested Eagles Lophaetus occipitalis fitted with geographic positioning system transmitters in an agricultural landscape in KwaZulu-Natal Province, South Africa. Mean home ranges (± SD) of males and females estimated using the autocorrelated kernel density estimator (AKDE) method were 608 ± 552 ha ( n = 5) and 664 ± 844 ha ( n = 4), respectively. Core areas (KDEhref 50%) were estimated as 80 ± 38 ha and 39 ± 20 ha for males and females, respectively. We also recorded exploratory behaviour (in the form of long excursions) in two of the birds, of up to 49 km from the centre of their home range. The relatively small home ranges reported in this study are suggestive of productive foraging habitats whereby Long-crested Eagles can meet their energy requirements without having to travel long distances to obtain resources. Consistent with predictions, non-breeding male and female Long-crested Eagles showed similar ranging behaviour, which includes occasional exploratory behaviour.